Pengembangan Pariwisata Heritage di Kawasan Konservasi Museum Abdul Jalil, Magelang - Mussadun Mussadun (Ruang, 2018)
Abdul Jalil Museum is one of the museums used as a means to protect the historic goods of the TNI Army. This museum is located in the same complex with the Military Academy in Magelang City. Magelang City is a city that has historical value so no wonder if many historical museums found here. The government took the initiative to make tour packages to visit the museums in Magelang City. With this discourse, Abdul Jalil Museum has an opportunity in heritage tourism potential as a means of education. This research was conducted to develop the heritage area of Abdul Jalil Museum to become one of the attractions of interest by tourists of Magelang city. Analysis of the significance of the heritage area of the museum is done to do the scoring so the conservation efforts that must be done on the region can be known. Then the analysis of conservation planning is done to know the aspects that need to be prepared and developed as an effort to utilize heritage area for tourism activities. Based on the results of the analysis shows that Abdul Jalil Museum has a high importance and included in the conservation group B. This museum also still requires efforts to develop a good aspect of tourism that can attract tourists to visit.